MENGATASI KENALAN REMAJA PADA SISWA SMA MELALUI PENERAPAN KURIKULUM MORALITAS DI INDONESIA - Hikmat (Globalwriting Academica Consulting & Publishing, 2019)
There are so many juvenile delinquencies that occur in Indonesia, especially for high school students. This delinquency causes various fights to brawls without any really important problems. Worse, these brawls often cause injury to death for the participating students. As a result, this problem causes concern for other students as well as parents. Understanding this problem can be carried out through the provision of religious values combined with education. This research will be carried out using a qualitative approach with data sourced from various research results and previous studies that are still relevant to this research. The results of this study found that there were efforts to be able to offer various things such as being honest, polite, democratic and living in harmony at the community level. As for the school level, it is necessary to make efforts to keep up with the various developments of the times by teachers. Then the teacher also needs to provide an example of a fairly commendable attitude so that later he can become a role model for his students.